Dear writer : pep talks & practical advice for the creative life - Smith, Maggie, 1977- (Washington Square Press/Atria, 2025)
"Drawing from her twenty years of teaching experience and her bestselling Substack newsletter, For Dear Life, Maggie Smith breaks down creativity into ten essential elements: attention, wonder, vision, play, surprise, vulnerability, restlessness, tenacity, connection, and hope. Each element is explored through short, inspiring, and craft-focused essays, followed by generative writing prompts"--